2011
DOI: 10.2147/ijgm.s19301
|View full text |Cite
|
Sign up to set email alerts
|

Associated congenital anomalies between neonates with short-gap and long-gap esophageal atresia: a comparative study

Abstract: Background:Predicting the presence of long-gap esophageal atresia (EA) prior to the surgery is of clinical importance. No comparison between short-gap and long-gap EA for the prevalence of VACTERL and non-VACTERL-type anomalies has yet been performed.Objective:The aim of this study was to compare VACTERL and non-VACTERL-type anomalies between patients with short-gap and long-gap EA.Methods:Retrospectively, medical records of all newborns managed for EA/tracheoesophageal fistula (TEF) in Tabriz Children’s Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…How can we reconcile our results with a previous study 14 that found no statistically difference in the occurrence VACTERL-associated anomalies between subjects with LGEA and non-LGEA? It is notable that the rate of detection of VACTERL anomalies was considerably higher in our study, raising the possibility that we detected these such anomalies with greater sensitivity.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…How can we reconcile our results with a previous study 14 that found no statistically difference in the occurrence VACTERL-associated anomalies between subjects with LGEA and non-LGEA? It is notable that the rate of detection of VACTERL anomalies was considerably higher in our study, raising the possibility that we detected these such anomalies with greater sensitivity.…”
Section: Discussionsupporting
confidence: 67%
“…For example, compared to other studies, we had a high proportion of LGEA patients that is attributable to our institution being a referral center for LGEA. 14 Our cohort included complex patients, often transferred from other facilities with complicated records and potentially inconsistent data collection, raising the possibility that despite all efforts some anatomical anomalies may have been missed. In addition, our CMA analysis covered only a subset of patients; this costly testing had been used clinically in only a subset of patients, and our study funds did not cover research-based testing for this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings of increased extra-axial space (viz. idiopathic external hydrocephalus without evidence of ventricular enlargement or hydrocephalus) and ventricular enlargement were previously reported in infants with LGEA [16,17,67]. Such findings have also been described as part of a benign condition in the absence of surgery [68][69][70][71] and as part of external hydrocephalus not associated with cerebral atrophy [72].…”
Section: Increased Csf Volume In Infancymentioning
confidence: 71%
“…Although some patients had VACTERL association (Table 1), none had concomitant hydrocephalus (viz. VACTERL-H) 48,49 , known to be of autosomal recessive or X-linked recessive inheritance [49][50][51][52] . Similarly, none of the subjects included in analysis had cardiac involvement (less severe cases).…”
Section: Discussionmentioning
confidence: 99%